2012
DOI: 10.1016/j.visres.2012.08.011
|View full text |Cite
|
Sign up to set email alerts
|

The human visual system uses a global closure mechanism

Abstract: Research asserting that the visual system instantiates a global closure heuristic in contour integration has been challenged by an argument that behaviorally-detected closure enhancement could be accounted for by low-level local mechanisms driven by collinearity or "good continuation" interacting with proximity. The present study investigated this issue in three experiments. Exp. 1 compared the visibility of closed and open contours using circles and S-contours from low to moderately high angles of path curvat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…Psychophysical studies show that adults exhibit a closure superiority effect ; that is, detectability of closed figures is enhanced relative to open figures (Kovács and Julesz, 1993; Mathes and Fahle, 2007; Machilsen and Wagemans, 2011; Gerhardstein et al, 2012). For instance, using a contour detection task with adults, Kovács and Julesz (1993) incrementally added co-aligned elements to a circular contour and found that performance was not enhanced until the contour was closed.…”
Section: Path To Object Perceptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Psychophysical studies show that adults exhibit a closure superiority effect ; that is, detectability of closed figures is enhanced relative to open figures (Kovács and Julesz, 1993; Mathes and Fahle, 2007; Machilsen and Wagemans, 2011; Gerhardstein et al, 2012). For instance, using a contour detection task with adults, Kovács and Julesz (1993) incrementally added co-aligned elements to a circular contour and found that performance was not enhanced until the contour was closed.…”
Section: Path To Object Perceptionmentioning
confidence: 99%
“…Closure therefore elicited a pop-out effect, by their interpretation. While there has been some contention regarding whether a global heuristic such as closure needs to be invoked to explain the closure superiority effect (Tversky et al, 2004), recent research (Gerhardstein et al, 2012) strongly suggests that such a mechanism does operate in the visual system. By separately manipulating collinearity and closure using circles and S contours, Gerhardstein et al (2012) showed that closure enhances detectability of a contour separate from local grouping heuristics.…”
Section: Path To Object Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contour integration studies typically present a set of collinear Gabor elements embedded in randomly oriented noise elements. Detection difficulty varies as a function of the extent of collinearity between contour elements (a straight line is easiest, Field et al, ; Hadad, Maurer, & Lewis, ), relative noise density (contours denser than or equal to surrounding noise are easier to detect; Kovács, ), eccentricity (Lev & Polat, ; Shani & Sagi, ) and closure (closed contours are easier to detect than open ones; Gerhardstein, Tse, Dickerson, Hipp, & Moser, ; Kovács, ; Kovács & Julesz, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also examined how grouping of local elements into a contour is further modulated by features arising on a larger scale. Factors such as the convexity or curvature of the contour (Bertamini & Wagemans, 2013), contour closure (Elder & Zucker, 1993;Gerhardstein, Tse, Dickerson, Hipp, & Moser, 2012;Kovacs & Julesz, 1993), symmetry (Machilsen, Pauwels and Wagemans, 2009); shape familiarity and predictability (Nygard, Sassi & Wagemans, 2011;Sassi et al, 2010Sassi et al, , 2014Sassi, Machilsen, & Wagemans, 2012) have all been shown to affect grouping or contour integration.…”
Section: Contour Integrationmentioning
confidence: 99%